Specialization and competitiveness: analysis of Brazilian exports of cocoa beans and products - Calmon da Conceição, Ronisson Lucas; Droguett Macedo, Renato Droguett; da Silva Gomes, Andréa; de Moura Pires, Mônica; Lisboa, Gustavo Joaquim; Espírito Santo, Monick Midlej do (Revista Mexicana de Ciencias Agrícolas, 2020)
Cocoa farming was and still is an economic activity of great importance for the economy of Brazil and the rest of the world. During the last few decades, African and Asian countries have increased their presence as producers, increasing global competition and leading to changes in Brazil’s participation in foreign markets. In this context, this study analyzes the competitiveness of Brazilian cocoa farming based on exports of cocoa beans and products (powder and press cake, cocoa butter and cocoa liquor).To do so, foreign trade indicators were calculated for the period from 1996 to 2016, in the form of: revealed comparative advantage (RCA); coverage ratio (CR); and trade balance contribution index (TBCI). The data showed that, from 1997, Brazil has moved from being an exporter to import cocoa beans, as a result of the significant drop in production and productivity of the agriculture of the state of Bahia, the largest exporter and importer of cocoa beans in Brazil. In several years, exports of cocoa butter accounted for the greatest contribution to foreign trade. In general, the indicators showed the poor competitive performance of Brazil in the international market of cocoa beans and products.The country lost market share and suffered the greatest loss of competitiveness in the export of such commodities. There is a need to formulate competitive strategies to support the cocoa industry in order to increase its global market share. This could involve conquering more dynamic or little-exploited markets, mainly for cocoa products which offer higher added value.